ARENDT’S PERSPECTIVE ON THE ROLE OF THE INTELLECT IN THE ACT OF AVOIDING EVIL - Shelomita Selamat (Jurnal Filsafat dan Teologi Katolik, 2018)
Human being is a rational animal who has the capability to think. The activity of thinking distinguishes man from other animals. Nevertheless, there are some people who do not use their capability to think. Many people just follow what other people said without really considering what they actually do. For Hannah Arendt, this is one of the factors that causes many evils have occurred in our daily life. Moreover, she used the term of the banality of evil to describe the evil that has happened because of the culprit’s inability to think. Therefore, she emphasized the importance of thinking in every human being. For her, thinking makes human to avoid grave evil.